2006
DOI: 10.4321/s0365-66912006001200007
|View full text |Cite
|
Sign up to set email alerts
|

Manifestaciones oftalmológicas del síndrome de Carney

Abstract: RESUMENCaso clínico: El Complejo de Carney (CNC) es un raro síndrome multineoplásico, autosómico dominante; caracterizado por presentar mixomas, lesiones pigmentadas en la piel, tumores endocrinos y manifestaciones oculares. Discusión: Analizamos los signos oftalmológicos de este síndrome, los cuales suelen preceder al componente más serio del mismo, el mixoma cardíaco.Palabras clave: Síndrome de Carney, trastornos pigmentarios, mixomas, tumores endocrinos. COMUNICACIÓN CORTA ABSTRACTCase report: Carney comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
7
0
2
Order By: Relevance
“…The most common ophthalmologic manifestations are facial and palpebral lentigines, pigmented lesions of the caruncle or conjuntival semilunar fold and eyelid myxomas 27, 28 . There are some reports of pigmented schwannomas of the uvea 29 .…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common ophthalmologic manifestations are facial and palpebral lentigines, pigmented lesions of the caruncle or conjuntival semilunar fold and eyelid myxomas 27, 28 . There are some reports of pigmented schwannomas of the uvea 29 .…”
Section: Clinical Featuresmentioning
confidence: 99%
“…There are some reports of pigmented schwannomas of the uvea 29 . The differential diagnosis of pigmented lesions of the conjunctiva includes melanocytic nevus, melanosis (congenital or acquired), malignant melanoma or drug induce secondary pigmentation 28, 30 .…”
Section: Clinical Featuresmentioning
confidence: 99%
“…O Complexo de Carney tem herança autossômica dominante, penetrância e expressividade variável, ligada a dois loci: 17q22-24 e 2p16, não condicionando diferenças no fenótipo da doença 10 . O gene PPKAR1A (proteinkinase A type 1a regulatorysubunit) localizado na banda 24 do braço longo do cromossoma 17 (17q24) seria o responsável por originar a doença; ou seja, os casos de complexo de Carney têm sido associados a mutações nesse gene.…”
Section: Discussionunclassified
“…O gene PRKAR1A tem ação supressora tumoral, sendo responsável pela produção da subunidade reguladora tipo 1-alfa da proteína quinase A. Esta proteína está envolvida com importantes vias da sinalização endócrina. A subunidade reguladora tipo 1-alfa inibe a função da proteína quinase A, e a mutação de PRKAR1A origina uma subunidade com função praticamente nula, aumentando por conseqüência a sinalização intracelular da proteína quinase A levando à hiperatividade endócrina e formação de tumores 8,10 .…”
Section: Discussionunclassified
“…The tumor did not recur or metastasize after almost 10 years of follow-up, and the patient died of unrelated causes. Molecular studies revealed a complex genome with multiple whole-chromosome losses including monosomy of chromosomes 1, 2 (including loss of CNC2 at 2p16), 14, 17 (including loss of a copy of PRAKA1 at 17q24.2), 18,19,21,22, and X. No monosomy 3 was observed.…”
mentioning
confidence: 99%